EVALUATION OF ANTIDEPRESSANT ACTIVITY OF FICUS THONNINGII ROOT IN ALBINO MICE - BALA, ANU; MALHOTRA, MEENAKSHI; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2025)
Objective: The present study aimed to evaluate the antidepressant effects of the ethanolic extract of Ficus thonningii (EERFT) in albino Swiss mice and to assess its potential as atherapeutic agent for depression. Methods: Preliminary phytochemical analysis of Ficus thonningii revealed the presence of phenolic compounds, proteins, tannins, glycosides, carbohydrates, starch, vitamins, and minerals. Acute oral toxicity testing was performed using EERFT at doses of 5, 50, 300, and 1000 mg/kg via the oral route, with no observed behavioral changes or toxicity. Based on these results, doses of 200 mg/kg and 400 mg/kg were selected for further evaluation. The antidepressant activity of EERFT was assessed using the Forced Swim Test (FST) and Tail Suspension Test (TST), with fluoxetine (10 mg/kg) as the standard drug. Results: In TST, the control group (0.9% w/v sodium chloride, 10 ml/kg) showed insignificant immobility, whereas EERFT at 200 mg/kg and 400 mg/kg significantly reduced immobility. Fluoxetine also demonstrated a significant reduction in immobility. In FST, the control group exhibited insignificant immobility and number of jumps, while EERFT at 200 mg/kg and 400 mg/kg significantly reduced immobility and increased the number of jumps. Fluoxetine produced similar significant effects. Conclusion: The results support the traditional use of Ficus thonningii for managing depression. The ethanolic extract demonstrated significant antidepressant activity in both FST and TST models, comparable to fluoxetine. These findings suggest that Ficus thonningii contains bioactive compounds with antidepressant properties, offering potential for the development of novel neuropsychiatric therapies.